Jumping From a Height a Dyadic Death - Karbeyaz, Kenan; Gündüz, Tarık; Balcı, Yasemin (The Bulletin of Legal Medicine, 2007)
Double suicide pact or suicides of the perpetrator following homicide (homicide-suicide) were described as dyadic death. Double suicide is very rarely than homicide-suicide. In addition, double suicides by falling from high are seen extremely rarely. In this study, a double suicide by fall from height in Eskişehir is presented because that these kinds of deaths are seen very rarely. Key words: Suicide, dyadic death, fall from height